Physical properties of Fe-doped CdS quantum dots: single dot rectifying diode application - Maity P.; Kumar R.; Jha S.N.; Bhattacharyya D.; Chatterjee S.; Pal B.N.; Ghosh A.K. (My University, 2025)
The domain of single-molecule based electronic devices has grown remarkably over the past decade by utilizing nanotechnology to improve the efficiency of device fabrication. However, most of the single-molecule devices are based on organic materials. Compared with organic molecules, quantum dots (QDs) are excellent owing to their crystalline nature, environmental stability, narrow emission band and quantum yield with tunable electronic and optoelectronic properties. Here, CdS:Fe QDs were synthesized and analyzed to assess their structural, optical, and electronic properties, and subsequently, they were implemented in fabricating single-dot rectifying diodes. EXAFS revealed the average coordination number of the doped Fe element. The ITO/TiO2/CdS:Fe quantum dot heterostructure rectifying diodes were grown by spin coating and were characterized using scanning tunneling microscopy (STM) at room temperature. STM images revealed the distribution of QDs over the substrate, and the spectra revealed the improved rectification behavior with tunneling up to ∼1000×, revealing their excellent diode functionality. Threshold voltage tuning from 1.62 eV to 0.83 eV indicated the application of these diodes for tunable electronics with low power consumption. Thus, these results indicate the promising use of CdS:Fe QDs for optimized ambient atmosphere rectifying diode applications, opening the way for innovative electronic devices with improved performance and functionality. © 2025 RSC.